ANALISIS PENGARUH SUKU BUNGA, INFLASI, KURS MATA UANG, IHSG DAN DANA KELOLAAN TERHADAP IMBAL HASIL REKSADANA SAHAM - Sujoko, * (Program Doktor Ilmu Ekonomi, 2009)
The main objective of the study is to examinal the effect of interest rate, inflation, foreign exchange rate, IHSG and management of fund on return mutual fund in Indonesia Stock Exchange. The technique sampling is purposive sampling. As much as twenty mutual fund as sample for this research .The result of the study show that variable of SBI is not significant effect on return mutual fund, with p value 0.0764.Variable of Inflation rate is significant effect on return mutual fund with p value 0.0018. Variable of foreign exchange rate is significant effect on return mutual fund on return mutual fund with p value 0.0000.Variable of IHSG is significant effect on return mutual fund with p value 0.0027. Variable of management of fund is not significant effect on return mutual fund.Â Key Word: Mutual Fund, Inflation Rate, Foreign Exchange Rate.